Using the ARIMA model to predict cataract disease in Baghdad Governorate - Inam Abboud Hussein (Iraqi Journal for Administrative Sciences, 2025)
In this research, ARIMA models were used to predict the number of cataract patients in Baghdad, as data from Ibn al-Haytham Eye Hospital was used. It was found that the ARIMA model (1,0,0) is the best model for the time series of cataract patients, and this is what was reflected in the indicators. Model accuracy tests: This model has been applied to forecast the coming months. It showed predictive accuracy according to accuracy tests.